Three-Dimensional Lattice Boltzmann Simulation of Two-Phase Flow Containing a Deformable Body with a Viscoelastic Membrane (Communications in Computational Physics, 2020)
The lattice Boltzmann method (LBM) with an elastic model is applied to thesimulation of two-phase flows containing a deformable body with a viscoelastic membrane.The numerical method is based on the LBM for incompressible two-phase fluidflows with the same density. The body has an internal fluid covered by a viscoelasticmembrane of a finite thickness. An elastic model is introduced to the LBM in orderto determine the elastic forces acting on the viscoelastic membrane of the body. In thepresent method, we take account of changes in surface area of the membrane and intotal volume of the body as well as shear deformation of the membrane. By using thismethod, we calculate two problems, the behavior of an initially spherical body undershear flow and the motion of a body with initially spherical or biconcave discoidalshape in square pipe flow. Calculated deformations of the body (the Taylor shape parameter)for various shear rates are in good agreement with other numerical results.Moreover, tank-treading motion, which is a characteristic motion of viscoelastic bodiesin shear flows, is simulated by the present method.